Students’ Motivation in Learning Listening by Using YouTube: Case Study - Umi Quina Indah Wati Poeryono; Yousef Bani Ahmad; Sidik Indra Nugraha (Universitas Muhammadiyah Enrekang, 2021)
Motivation is a critical component in encouraging language learning. Gifted language learners might also underperform due to a lack of motivation. This study aims to determine what factors impact students' motivation to learn listening through YouTube. employing a case study, the experience of 8 Universities of Singaperbangsa Karawang students was gathered by means of questionnaire and interview. The findings enable students to strive to enhance their listening abilities and discover new vocabulary, as well as speed and comprehension pronunciation. Furthermore, giving audio and pictures on YouTube makes studying more engaging and allows students to memorize the words or phrases they hear. it seems that students' motivation in learning to listen using YouTube is influenced by factors in intrinsic and extrinsic motivation. Abstrak Motivasi adalah komponen penting dalam mendorong pembelajaran bahasa. Pembelajar bahasa berbakat mungkin dapat berkinerja buruk karena kurangnya motivasi. Penelitian ini bertujuan untuk mengetahui faktor-faktor apa saja yang mempengaruhi motivasi siswa belajar mendengarkan melalui YouTube. Dengan menggunakan studi kasus, pengalaman 8 mahasiswa Universitas Singaperbangsa Karawang dikumpulkan melalui angket dan wawancara. Temuan memungkinkan siswa untuk berusaha untuk meningkatkan kemampuan mendengarkan mereka dan menemukan kosa kata baru, serta kecepatan dan pemahaman pengucapan. Selain itu, memberikan audio dan gambar di YouTube membuat pembelajaran lebih menarik dan memungkinkan siswa untuk menghafal kata atau frasa yang mereka dengar. Nampaknya motivasi siswa dalam belajar menyimak menggunakan youtube dipengaruhi oleh faktor motivasi intrinsik dan ekstrinsik